2010
DOI: 10.1002/pc.20953
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of glass bead‐ and wollastonite‐filled isotactic‐polypropylene composites modified with thermoplastic elastomers

Abstract: Mechanical properties of the isotactic-polypropylene/ glass bead (iPP/GB) and iPP/wollastonite (iPP/W) composites modified with thermoplastic elastomers, the poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer (SEBS) and corresponding block copolymer grafted with maleic anhydride (SEBS-g-MA), were investigated. An increase in toughness of iPP with the elastomers was associated with a decrease in rigidity and strength. Mechanical performance of iPP increased more with acicular W than with spherical GB due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 111 publications
0
34
1
Order By: Relevance
“…As expected, the incorporation of spherical fillers as well as the change in the T Ch influences the impact behavior of the printed parts ( Figure ). Independent of the processing conditions, all the composites exhibit a notched impact energy decreased by 70–90% compared to neat PP, because the incorporated microspheres can act as initiation points for defects and can reduce the impact fracture area . A similar decrease in the impact energy by 65% to 80% was observed for 3D‐printed Charpy specimens of the same PP compound filled with the broadly distributed glass spheres Spheriglass 3000E in a previous work .…”
Section: Resultscontrasting
confidence: 92%
“…As expected, the incorporation of spherical fillers as well as the change in the T Ch influences the impact behavior of the printed parts ( Figure ). Independent of the processing conditions, all the composites exhibit a notched impact energy decreased by 70–90% compared to neat PP, because the incorporated microspheres can act as initiation points for defects and can reduce the impact fracture area . A similar decrease in the impact energy by 65% to 80% was observed for 3D‐printed Charpy specimens of the same PP compound filled with the broadly distributed glass spheres Spheriglass 3000E in a previous work .…”
Section: Resultscontrasting
confidence: 92%
“…Previous studies by the authors showed that the stiffness of neat PP is sufficient for the use in FFF. As the incorporation of glass‐spheres in PP increases the Young's modulus , the stiffness requirement related to 3D‐printing is met by all filled composites of the present work. However, it was shown that only filled polypropylene compounds with a strength of minimum 13 MPa were successfully printable using a similar printing setup as described in “Impact Specimen Preparation” [2].…”
Section: Resultsmentioning
confidence: 78%
“…Their geometry allows good dispersion and a close packing, resulting in an improved dimensional stability for different thermoplastics . So far, many studies have been devoted to PP filled with the conventionally used inorganic soda lime glass, also known as A‐glass . Other glass types, such as the borosilicate glass (E‐glass), have established themselves as the filling material of choice for glass‐fiber reinforced composites , also in connection with PP .…”
Section: Introductionmentioning
confidence: 99%
“…By integrating the stress-strain curves in Figure 6(c), the toughness of material can be obtained. 36 It is 39.03 MJ/m 3 for composites, nearly 14 folds of the toughness (2.62 MJ/m 3 ) of pure epoxy resin, demonstrating that the composites have good balance of strength and ductility.…”
Section: Analysis Of the Rtm Process For Fabricating Cnt/ Epoxy Compomentioning
confidence: 97%